Piano Sonata no. 20 in G major, op. 49, no. 2, edited by Macpherson - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Macpherson, S. (Stewart), 1865-1941 (editor):::Contributor:::::::::::: (London; United Kingdom; Joseph Williams, 2023)
Separate issue of the Piano Sonata no. 20 in G major, op. 49, no. 2, in an analytical edition prepared by Stewart Macpherson and first published by Joseph Williams in London in 1914; revised printing, 1939 (copyright renewed in 1942).